Energy densities of key prey species in the California Current Ecosystem - Price, Samuel E.; Savoca, Matthew S.; Kumar, Mehr; Czapanskiy, Max F.; McDermott, Dane; Litvin, Steven Y.; Cade, David E.; Goldbogen, Jeremy A. (Frontiers in Marine Science, 2024)
The energetic content of primary and secondary consumers is central to understanding ecosystem functioning, community assembly, and trophodynamics. However, these foundational data are often limited, especially for marine ecosystems. Here we report the energy densities of important prey species in the California Current Ecosystem. We investigated variation in energy density within and between species and explored potential underlying causes of these differences. Northern anchovy (Engraulis mordax) is the most energy dense of the species analyzed with a median value nearly twice as high as was found in krill (Euphausia pacifica and Thysanoessa spinifera). Relationships with body size varied among species; krill energy density increased, with both length and wet weight. In addition, we find that anchovy, sardine (Sardinops sagax), and market squid (Doryteuthis opalescens) have higher energy content in the summer and fall as compared to the spring. This aligns with the ecosystem phenology of strong upwelling during spring (March – May) driving high primary productivity, followed by widespread predator presence through the summer and fall (June – October). Our results inform food web studies in the California Current and suggest new avenues for investigating differences in species and ecosystem energetics in an era of rapid global change.